Challenges and in Museum Education, Best Practices in Hungary - Kempf, Katalin; Vincze, Beatrix; Németh, András (Rivista di Storia dell’Educazione, 2020)
The study aims to present the best practices of museum education, art pedagogy and circus pedagogy in Hungary, to highlight their importance and their role as mediators of cultural values and their role in social equal opportunities. It emphasizes the role of non-formal forms of learning that are capable of meeting learners’ needs in a well-defined, differentiated, and experiential way outside the school system. At the same time, the study reflects on current issues in the renewal of museum education. Among other things, for those who want to study, «everything is more interesting outside of school». Changing learning habits and technical opportunities poses a major challenge in sustaining learning motivation. It also emphasizes the potential of informal learning in diverse settings - family, community, informal and supportive of information acquisition and capacity building (Coombs 1969, 1972). It cites examples of good domestic practice as interpreted by the Constructivist Museum (Anderson 2008; Black 2012; Hein 2004 a, b) and refers to programs, projects, and circus pedagogical initiatives for SEN and disadvantaged groups.